2023
DOI: 10.1136/bmjopen-2023-078618
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent factors shaping vulnerability to underage entry into sex work: a quantitative hierarchical analysis of female sex workers in Nairobi, Kenya

Pooja Shah,
Rhoda Kabuti,
Alicja Beksinska
et al.

Abstract: ObjectiveTo explore factors associated with early age at entry into sex work, among a cohort of female sex workers (FSWs) in Nairobi, Kenya.BackgroundYounger age at sex work initiation increases the risk of HIV acquisition, condom non-use, violence victimisation and alcohol and/or substance use problems. This study aimed to understand factors in childhood and adolescence that shape the vulnerability to underage sex work initiation.DesignBuilding on previous qualitative research with this cohort, analysis of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Our findings on how women joined sex work or would leave are consistent with published literature. Earlier research showed that women joined due to economic need, or because of earlier traumatic experiences of sexual abuse, and they would leave if they achieved economic stability [ 16 , 21 , 35 ]. This further highlights the importance of continued efforts to empower all women, and protect them from sexual violence, regardless of their level of education, status of work, and where they recruit or provide services to their clients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on how women joined sex work or would leave are consistent with published literature. Earlier research showed that women joined due to economic need, or because of earlier traumatic experiences of sexual abuse, and they would leave if they achieved economic stability [ 16 , 21 , 35 ]. This further highlights the importance of continued efforts to empower all women, and protect them from sexual violence, regardless of their level of education, status of work, and where they recruit or provide services to their clients.…”
Section: Discussionmentioning
confidence: 99%